Blowing up a rats nest :crime externalities of the police intervention of Bogotá's "The Bronx" (2018)
Understanding crime reallocation and persistence after a spatially targeted large police operation is crucial for public policy design. This paper assesses the spatial spillovers, the persistence over time and the impact on the treated area of the largest targeted security intervention ever witnessed in Bogotá, on a place called "The Bronx" in 2016, that hosted the main narcotic cartels and criminal gangs of the city. Using difference- in-differences, I show that the common perception that the intervention made the city more insecure is largely wrong. I do find that specific crimes displaced, but for a relatively short period. This is largely due to the fact that the operation in "The Bronx" was accompanied by smaller interventions in other hot spots. Using a synthetic control method, I find a generalized and significant crime reduction in the treated area, the number of personal robberies decreased by 48.6%, phone thefts by 44.8%, personal injuries by 36.8%, homicides by 29.8% and vehicle thefts by 47.2%